How to Observe the Sun Safely - Macdonald, Lee. (The Patrick Moore Practical Astronomy Series,, 2012)
How to Observe the Sun Safely, Second Edition gives all the basic information and advice the amateur astronomer needs to get started in observing our own ever-fascinating star. Unlike many other astronomical objects, you do not need a large telescope or expensive equipment to observe the Sun. And it is possible to take excellent pictures of the Sun with today's low-cost digital cameras! This book surveys what is visible on the Sun and then describes how to record solar features and measure solar activity levels. There is also an account of how to use H-alpha and Calcium-K filters to observe and record prominences and other features of the solar chromosphere, the Sun's inner atmosphere. Because we are just entering a period of high activity on the Sun, following a long, quiet period, this is a great time to get involved with solar observing. Still emphasizing safety first, this Second Edition reflects recent and exciting advances in solar observing equipment. Chapters 6 through 8 have been completely revised to allow amateur astronomers to compare observing the Sun using digital vs. film cameras and all the latest advances in image processing. Finally, this new edition also includes more than twice as many illustrations as the first, almost half of them new images.